Congenital and Developmental Abnormalities of the Hand and Wrist - Vanhoenacker, Filip M.; Simoni, Paolo; Bosmans, Frederik; Boutry, Nathalie (Seminars in Musculoskeletal Radiology, 2021)
Identification of congenital skeletal abnormalities is complex because of the large variety of individual syndromes and dysplasias that are often difficult to remember. Although a correct diagnosis relies on a combination of clinical, radiologic, and genetic tests, imaging plays an important role in selecting those patients who should be referred for further genetic counseling and expensive genetic tests. In addition to information derived from radiologic analysis of other skeletal elements, radiographs of the hand and wrist may provide particular useful information. In the first part of this article, we provide a guide for a systematic radiologic analysis of the hand and wrist bones that may help characterize congenital and developmental diseases. Special attention is given to the use of correct terminology. In the second part, we discuss typical examples of congenital and developmental diseases involving the hand and wrist, with an emphasis on skeletal dysplasias.
Keywords: Hand; Wrist; Radiography; Congenital; Developmental